School-based individual therapy for children with behavior problems - Rosenberg, Josie, author; Biringen, Zeynep, advisor; Barrett, Karen, committee member; Harvey, Ashley, committee member; Kogan, Lori, committee member (Colorado State University. Libraries, 2011)
This study was conducted to assess the impact of individual child therapy for children aged 5-11 who exhibit classroom misbehavior. We hypothesized that the emotional availability of children would significantly increase and that reports of behavior problems would significantly decrease over the course of a school-based child therapy intervention. The Emotional Availability (EA) Scales (Biringen, 2008) were used to assess child therapeutic engagement. (Biringen & Easterbrooks, 2000). Therapy sessions were taped monthly to assess the child's EA. Disciplinary referral data and teacher reports of behavior problems using the Teacher Report Form (TRF) (Achenbach,1991) were collected pretest and posttest. Results indicated a significant reduction in disciplinary referrals, but no significant changes in teacher reports or EA scores. Implications and future directions for research are discussed.
Keywords: child therapy; school-based intervention